An Outbreak of Aeromonas hydrophila Infection in Turtles (Pseudemis scripta) - Pasquale, Vincenzo (1994)
An outbreak of Aeromonas hydrophila infection with a high rate of mortality (95%) in turtles (Pseudemis scripta) in Italy is reported. Pure cultures of the pathogen were isolated from liver, lung, kidney, and heart specimens of the turtles. The A. hydrophila isolate was resistant to amoxicillin, ampicillin, cephalothin, and trimethoprim-sulfamethoxazole but was sensitive to a number of other antibiotics tested. The study indicates that pet turtles can act as reservoirs of this pathogen and may play an important role in the etiology of Aeromonas-associated human infections.